2014
DOI: 10.1162/edfp_a_00147
|View full text |Cite
|
Sign up to set email alerts
|

So Slow to Change: The Limited Growth of Nontax Revenues in Public Education Finance, 1991–2010

Abstract: We examine changes in the use of nontax revenues for education finance from 1991 to 2010. Beyond the summary of usage over time, we ask whether nontraditional revenues like fees accentuate or mitigate the impact of downturns. More generally, we examine the extent to which school districts have responded to fiscal pressures by turning to nontax revenues. We also document the extent to which the use of nontax revenues varies across districts according to student poverty status. We show that alternative revenues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Second, property taxes constitute the lion's share of own-source revenue for most school districts in the U.S. Therefore, when confronted with a constraining limit on property taxes, they are less able to raise adequate other own-source revenues to offset the shortfall, as confirmed by the historical analysis in Downes and Killeen (2014). Also, the constraining effects of TELs on school districts may become stronger over time (Dye, McGuire, and McMillen 2005).…”
Section: <A>3 Literature Reviewmentioning
confidence: 98%
“…Second, property taxes constitute the lion's share of own-source revenue for most school districts in the U.S. Therefore, when confronted with a constraining limit on property taxes, they are less able to raise adequate other own-source revenues to offset the shortfall, as confirmed by the historical analysis in Downes and Killeen (2014). Also, the constraining effects of TELs on school districts may become stronger over time (Dye, McGuire, and McMillen 2005).…”
Section: <A>3 Literature Reviewmentioning
confidence: 98%
“…In our previous work, Downes and Killeen (2014) found that the use of fees was higher in districts in states in which districts were subject to TELs, but the authors could not determine the extent to which there was significant within-state variation in the use of alternative revenues in states with limits in place. Colorado gives us the opportunity to see if there is such within-state heterogeneity.…”
Section: Why Colorado?mentioning
confidence: 87%
“…Downes and Killeen (2014) found that one of the few consistent determinants of the use of fees and other alternative revenue sources was the presence of limits on the ability of localities to raise revenues or increase expenditures. However, the authors of that paper could only include relatively crude controls for the presence of local TELs, given the national nature of the analysis.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations